Software Defect Prediction For Quality Evaluation Using Learning Techniques Ensemble Stacking - Kusuma, Muhammad Romadhona; Windu Gata; Sigit Kurniawan; Dedi Dwi Saputra; Supriadi Panggabean (Pusat Penelitian dan Pengabdian Pada Masyarakat Sekolah Tinggi Manajemen Informatika dan Komputer AKBA Makassar, 2023)
This research aims to improve the software quality and effectiveness of zakat management by the National Amil Zakat Agency (BAZNAS) through the development of a software defect prediction model (SDPM). We used machine learning techniques and ensemble stacking approach on the